Slow learning of feeding skills in a nocturnal extractive forager. (March 2021) - Maynard, Keely Q.; Birot, Hélène; Campera, Marco; Imron, Muhammad Ali; Jasso del Toro, Cristina; Poindexter, Stephanie A.; Nekaris, K.A.I.
Abstract : A long developmental period in animals is often needed to learn skills for adult reproduction and survival, including feeding behaviour. The nocturnal Javan slow loris, Nycticebus javanicus, is unusual in that it consumes a specialized diet of difficult to extract resources, as well as disperses up to a year after sexual maturity. Here, we examined the ontogeny of its feeding behaviour to understand whether learning to feed on difficult resources, including by co-feeding, is related to delayed dispersal. We collected feeding and proximity data on developing and adult wild slow lorises at a long-term field site in Cipaganti, West Java from 2012 to 2018. To determine whether acquisition of insects, exudates, nectar and flowers varied by age, we ran logistic generalized additive mixed models. We found that intake of insects and exudates occurred significantly more in the early stages, and feeding on nectar significantly more in the later stages, of development. Co-feeding occurred for all food types, with insects showing the most co-feeding events during early development, and co-feeding on exudates remaining high throughout development. Social learning via co-feeding is a potentially important factor in transmission of dietary information from older individuals, including siblings and parents, to young slow lorises. Differences between immature and adult diets levelled off after sexual maturity and before average dispersal. Together these factors suggest that the period required to learn to forage on difficult items could help explain the delayed dispersal patterns seen in mammals with similar foraging strategies. Highlights: Javan slow lorises show ontogenetic changes of difficult to eat foods. Javan slow lorises co-feed in pairs and groups on gum, insects and nectar. Lorises achieve adult diet after sexual maturity, dispersing a year later.